Analisis Faktor-Faktor Yang Mempengaruhi Minat Berwirausaha Pada Mahasiswa Program Studi Akomodasi: Studi Kasus Di Akademi Komunitas Mapindo - Ni Putu Oka Ariantini (Universitas Triatma Mulya, 2025)
This study aims to analyze the factors influencing entrepreneurial interest among students of the Accommodation Study Program at the Indonesian Community Academy of Hospitality Management (AK Mapindo). This research employs a descriptive qualitative approach using a case study method. Data were collected through semi-structured interviews with five active students selected purposively based on their interest in entrepreneurship. Thematic analysis was used to identify emerging patterns related to motivation, obstacles, and support influencing entrepreneurial interest. The findings indicate that internal factors such as self-confidence, entrepreneurial practice experiences on campus, and interest in creativity and independence significantly influence students’ desire to start their own businesses. On the other hand, external factors such as family support, social environment, and encouragement from lecturers and curriculum also play an important role. However, challenges such as limited capital, lack of access to advanced training, and insufficient entrepreneurial guidance were identified as inhibiting factors. These findings are expected to serve as a foundation for developing more contextual and relevant entrepreneurial education strategies tailored to the needs of vocational students.